Efek Imunomodulasi Ekstrak Etanol Kaempferia galanga terhadap Proliferasi Sel Limfosit Secara In Vitro - Dianita Dwi Sugiartanti; Ening Wiedosari (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Kaempferia galanga L. is a traditional medicine with antitumor properties, as indicated by its immunomodulatory activities. This study aimed to determine the effect of K. galanga on lymphocyte cell proliferation activity as an indicator of immunomodulatory properties. This study was conducted at the Indonesian Research Center for Veterinary Science (February to April 2018). The immunomodulatory activity of the extract was evaluated with an in vitro splenocyte proliferation assay. The assay was based on cellular enzymatic synthesis to transform the XTT from formazan tetrazolium as an indicator. The K. galanga extract was obtained by 96% ethanol extraction. The test was conducted in an aseptic condition, consisted of five treatment groups with three replications each. Three groups of splenocyte cell culture, each with extract concentration of 2.5 µg.ml-1, 25 µg.ml-1, and 250 µg.ml-1, as well as a positive (Concanavalin A/Con A) and negative (cell only) control. The cell suspension (10x104 cells/ml) was distributed on 96-well plates and cultured following the treatment groups. The same five plates were made for five days of observation and retrieved daily by observing an Elisa reader at 450 nm. The extract of K. galanga at 2.5 µg.ml-1, 25 µg.ml-1, and 250 µg.ml-1 significantly (P <0.05) promoted splenocyte proliferation compared to control. Therefore, it was expected that K. galanga has a high potential to be used as immunomodulators. Hence, further investigations should be done to clarify the mechanisms of the immunomodulatory effect of K. galanga as an antitumor in vivo.